THE UTILIZATION OF DUOLINGO TO BOOST STUDENTS’ GRAMMAR MASTERY IN SENIOR HIGH SCHOOL - Dian Fadhilawati; Moh Mansur; Suyitno (Universitas Islam Balitar, 2023)
This classroom action research utilized Duolingo to enhance the grammar mastery of 31 senior high school students in Reported Speech. The research procedures cover; planning, acting, observing, and reflecting. The researchers collected data through tests. The results demonstrated a significant improvement in students' grammar of Reported Speech mastery, with test average scores increasing from 56.77 to 85.16. Regarding the result, teachers are suggested to integrate technology-based learning tools like Duolingo to create engaging and interactive learning environments and enhance students‘ mastery. However, it is important to note that individual student progress varied, and some students showed more substantial improvements compared to others. Further analysis and consideration of factors such as individual learning styles, frequency of Duolingo usage, and additional instructional support may help understand the variations in student performance.